Diseminasi Teknologi Lampu Darurat Berbahan Air Garam di Desa Ekoharjo Kabupaten Lampung Tengah - Irza Sukmana; A Y E Risano; M. Arif Wicaksono; Sugiyanto Sugiyanto; Nafrizal Nafrizal; M. Badaruddin (Edumedia Solution, 2022)
Electrical energy is needed and continues to increase in line with the population and economic growth, including in Lampung Province. Problems may occur once happen the rotating power outages, in this case the community uses candle or kerosene lamps. The use of candle or kerosene lamps may cause danger due to the combustion gas produced and a potential of fire. Therefore, it is necessary to make efforts to produce alternative energy sources in energy renewal, one of which is to build a salt water electrical energy source using the sea cell method, to build an energy independent village. Electricity through electrochemistry is one of the alternative electrical energy that can be generated by utilizing an oxidation-reduction process in which an electrochemical cell with a pair of Cu(Ag)-Zn electrodes is used. The electrodes are made of Cu fibers with a length of 2 m per strand as many as 25 strands and a Zn plate with dimensions of 10 cm long and 3.5 cm wide. Cu is coated with Ag metal using the electroplating method, while Zn metal is protected with Mg metal as a sacrificial anode. The electrical energy produced from this lamp is expected to be applied as renewable energy in a sustainable manner. The University of Lampung has a very good relationship with Ekoharjo village in Central Lampung district of Lampung Province.